Trace elements in soils and plants - Kabata-Pendias, Alina, (CRC Press, 2010)
"This fourth edition of a bestseller reflects the explosion of research during the past decade regarding trace elements and the environment related to the soil-plant system. It provides information on the biogeochemistry of trace elements in the soil-plant system and how these elements control our food quality. It discusses the assessment of natural/background content of trance elements in soil, bioindication of chemical status of environmental compartments, soil remediation, and hyperaccumulation and phytoextraction of trace metals from the soil. The table of contents reflects the IUPAC's recommendation for numbering element groups, giving the new edition an updated organizational flow"--